2019
DOI: 10.1108/ijpdlm-11-2019-399
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management and Industry 4.0: conducting research in the digital age

Abstract: Supply chain management and Industry 4.0: conducting research in the digital age Introduction In essence, Industry 4.0[1] enables an automated creation of goods and services as well as supply and delivery, which functions largely without human intervention. Industry 4.0 is happening now (Vogel-Heuser and Hess, 2016, Sprovieri, 2019) and describes the trend toward automation and data exchange in manufacturing technologies and processes which include among others cyber-physical systems (CPS), industrial Internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(138 citation statements)
references
References 37 publications
0
134
0
4
Order By: Relevance
“…This implies utilizing technologies to minimize dependence on human between firms. Ralston and Blackhurst (2020) , HYPERLINK \l "bib78" Tan et al., (2019); Hofmann et al., (2019) . Localization/ regionalization of sourcing Sourcing (and processing) are localized within the same region to meet the local demand and reduce supply chain integrations.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies utilizing technologies to minimize dependence on human between firms. Ralston and Blackhurst (2020) , HYPERLINK \l "bib78" Tan et al., (2019); Hofmann et al., (2019) . Localization/ regionalization of sourcing Sourcing (and processing) are localized within the same region to meet the local demand and reduce supply chain integrations.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Proactive strategies are primarily technology-driven strategies that rely on developing technical infrastructures, such as digital connectivity and supply chain automation to avoid future disruptions ( Ralston and Blackhurst, 2020 ; Tan et al., 2019 ; Hofmann et al., 2019 ). Iakovou et al.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, cybersecurity is endangered in terms of loss of confidentiality, integrity, and availability of data associated with networked manufacturing machines (Corallo et al 2020). Many experts anticipate significant impacts in the supply chain management segment (Dev et al 2020;Hofmann et al 2019), which can be identified as security risks associated with the interconnection cyber processes into international digital structures.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many manufacturing and service companies are going through the stage of digital transformation, radical revision of the main business processes, increasing the flexibility of solutions, business transparency for stakeholders and improving reputation [3]. First, there is a rethinking of supply chains, using digital platforms that aims to support the transparency and velocity of material flows, promoting their decentralization and real time management [4], [5]. Second, digitalization improves the financial culture and financial performance of banks [6].…”
Section: Introductionmentioning
confidence: 99%